Analysis of OAM Mode Purity of Integrated Optical Vortex Beam Emitters - Changzheng Sun; Juan Zhang; Bing Xiong; Jian Wang; Zhibiao Hao; Lai Wang; Yanjun Han; Hongtao Li; Yi Luo (IEEE Photonics Journal, 2017)
A theoretical analysis is presented to investigate the orbital angular momentum (OAM) mode purity of microring-resonator-based integrated optical vortex emitters. By extending the dipole model for integrated vortex emitters, the influence of optical losses and grating imperfections on OAM mode purity of the output beam is investigated, thus clarifying the mode purity performance of the device in many practical scenarios. This work provides an efficient tool for the design of emitters with high OAM mode purity for optical communications or quantum information processing.